Islamic finance education for university students: a scoping review of the Scopus database - Riyad Moosa; Ahmed Mohammadali Haji (Intelektual Pustaka Media Utama, 2026)
Universities must catch up in providing the Islamic financial services industry (IFSI) with a trained and competent workforce. The discrepancy between university offerings and the IFSI’s needs highlights a research gap in this field. To address this gap, we scoped the academic literature in the Scopus database on higher education for the IFSI involving university students. The research question guiding this scoping review was: what is known about Islamic finance education for university students in higher education literature? The findings of this study map the scope of research in this area, including the various research themes explored within this domain. For instance, a maximum of 15 articles were identified in line with the research question, covering four themes: talent development in Islamic banking education, curriculum and education quality, student career aspirations and intentions, and e-learning and technology in education. Most studies were conducted in Malaysia, and similarly, most studies utilized a quantitative approach based on surveys. Finally, research gaps are identified for further exploration based on the themes identified in the study.